Expression of Chicken Toll-Like Receptors and Signal Adaptors in Spleen and Cecum of Young Chickens Infected with Eimeria tenella - ZHOU, Zuo-yong; HU, Shi-jun; WANG, Zhi-ying; GUO, Zhi-li; QIN, Bo; NIE, Kui (Journal of Integrative Agriculture, 2014)
Toll-like receptors （TLRs） are a group of highly conserved molecules which initiate the innate immune response to pathogens by recognizing structural motifs of microbes. Understanding the changes in chicken Toll-like receptors （ChTLRs） and signal adaptors expression that occur with Eimeria tenella infection will help to elucidate the molecular basis of immune control of coccidiosis caused by Eimeria. The present study detected the dynamic changes in the expression of ChTLRs and associated signal adaptors in the spleen and cecum ofE. tenella-infected chickens during the early stage of infection. The results showed that the expression peak for ChTLRs, MyD88 and TRIF occurred at 12 h post-infection （hpi）, ChTLR3, ChTLRI 5 and MyD88 mRNA expression in the spleen ofE. tenella infected chickens were significantly higher （P〈0.05） than that of negative control chickens, and there were similar tendencies of these molecules expression in the cecum and spleen of E. tenella-infected chickens. The expression of MyD88 was upregnlated at four time points in the cecum of E. tenella-infected chickens. The results of this study indicate that ChTLR3, ChTLR15 and MyD88 play a role in young chickens infected with E. tenella.